How Can Nurses Survive Bullying Environments? The Hollow Theory - Green, Cheryl; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
The Hollow Theory examines the emergence of toxicity in the workplaces of nurses. This book explores the origins of bullying and incivility as the profession of nursing emerges as a vulnerable one for insecure bullies to prey upon the focused and productive employee in order to elevate their own self-perceived personal and professional deficits. Toxic workplaces are maintained to control others and negatively impact affected persons who do not adapt to the dysfunction and choose to be true to themselves both personally and professionally. Healthy workplaces exist when healthy people take back control of the workplace by alleviating toxic norms (e.g., bullying, rudeness, lying, etc.). This book will help nurse leaders to support impacted nurses.
Dysfunction Within a Profession of Caritas -- Origins of The Hollow -- Structured Workplace Chaos -- Patients Matter -- Unprovoked -- Shallow -- The Depths of Forgetfulness -- The Depths of Regret -- Simplifying Life -- A Coverage of Eyes and Ears -- Is a state of calm achievable? -- Arise and Journey More.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Nursing; Nursing